ASSESSMENT OF HEAVY METAL CONTAMINATION IN SOILS AND VEGETABLE CROPS FROM SHARADA INDUSTRIAL ZONE, KANO STATE, NIGERIA - Suleiman, Kabiru; Ibrahim, Abdullateef Abdullahi (FUDMA JOURNAL OF SCIENCES, 2025)
Heavy metal accumulation in agricultural soils and vegetables near industrial zones poses a significant threat to food safety and public health. This study assessed the concentrations of Fe, Zn, Cu, Cd, Ni, Pb, and Cr in soils and edible parts of onion (Allium cepa), carrot (Daucus carota), and spinach (Spinacia oleracea) collected from three irrigation farms in the Sharada industrial area, Kano State, Nigeria. A total of 36 composite samples were analysed using atomic absorption spectroscopy (AAS). Results revealed that cadmium levels in spinach reached 0.44 mg/kg, exceeding the WHO/FAO limit (0.1 mg/kg) by 340%. Lead concentrations in carrots (0.33 mg/kg) and spinach (0.49 mg/kg) also surpassed the permissible threshold of 0.3 mg/kg, while Pb in soil peaked at 1.05 mg/kg, more than three times the allowable limit. Chromium levels in soil were similarly elevated (1.05 mg/kg), though plant uptake remained low. Strong positive correlations between Pb and Zn (r > 0.90) and between Cr and Zn (r > 0.90) indicate likely shared sources, such as industrial effluents and vehicular emissions. The findings recommend strict regulatory enforcement, continuous environmental monitoring, and remediation strategies, such as soil amendments and safer irrigation practices, to reduce human health risks and ensure sustainable crop production.
Keywords: Heavy Metals; Food Safety; Industrial Effluent; Spinach; Soil Contamination; Kano State